2000
DOI: 10.1029/1999jb900441
|View full text |Cite
|
Sign up to set email alerts
|

Modeling anisotropy and plate‐driven flow in the Tonga subduction zone back arc

Abstract: Abstract. The goal of this study is to determine whether shear wave splitting observed in subduction zone back arc regions, the Tonga subduction zone in particular, can be quantitatively modeled with flow in the back arc mantle driven by the motions of the subducting slab and the upper back arc plate. We calculated two-dimensional mantle flow models using known Tonga plate motions as boundary conditions and assuming a range of uniform and variable viscosity structures. Shear wave splitting was predicted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 42 publications
2
85
1
Order By: Relevance
“…These observations of trench-parallel fast directions contradict the predictions of simple cornerflow models for flow in the mantle wedge, in which viscous coupling between the downgoing slab and the overlying wedge material induces flow that is parallel to the convergence direction (e.g., Fischer et al, 2000). However, new laboratory results have shown that when olivine aggregates are deformed under high-stress, lowtemperature, water-rich conditions, the fast axes of individual olivine crystals tend to align 90 • from the flow direction (Jung and Karato, 2001).…”
Section: Introductioncontrasting
confidence: 41%
See 3 more Smart Citations
“…These observations of trench-parallel fast directions contradict the predictions of simple cornerflow models for flow in the mantle wedge, in which viscous coupling between the downgoing slab and the overlying wedge material induces flow that is parallel to the convergence direction (e.g., Fischer et al, 2000). However, new laboratory results have shown that when olivine aggregates are deformed under high-stress, lowtemperature, water-rich conditions, the fast axes of individual olivine crystals tend to align 90 • from the flow direction (Jung and Karato, 2001).…”
Section: Introductioncontrasting
confidence: 41%
“…Some contribution to the observed signal from the crust is likely in this splitting dataset, but anisotropy in the crust cannot explain the observed δt values up to nearly 2 s. The crustal thickness in the Ryukyu arc, ∼35-40 km (Taira, 2001), is insufficient to explain such large splitting, and observed crustal splitting times in Japan average about 0.2 s (Kaneshima, 1990). It has been demonstrated that both lithospheric and asthenospheric contributions to anisotropy are important in many regions (e.g., Fouch et al, 2000;Simons et al, 2002;Simons and van der Hilst, 2003;Fischer et al, 2005;Waite et al, 2005), although splitting measurements in subduction zone settings are nearly always interpreted in terms of flow in the asthenosphere (e.g., Fischer et al, 1998Fischer et al, , 2000Smith et al, 2001;Anderson et al, 2004). The lithosphere beneath the Ryukyu arc stations is likely to be thin, due to thermal erosion associated with mantle wedge flow (e.g., Conder et al, 2002), and it is unlikely that the lithosphere is thick enough to explain the large split times.…”
Section: Frozen Anisotropy In the Lithosphere And/or Crustmentioning
confidence: 99%
See 2 more Smart Citations
“…Knowing the distribution of seismic anisotropy can help address these issues (e.g., . The presence of anisotropy in the upper mantle beneath subduction zones has been well established (e.g., Ando et al, 1983;Fischer and Yang, 1994;Hiramatsu and Ando, 1996;Fouch and Fischer, 1996;Iidaka and Obara, 1997;Fischer et al, 1998Fischer et al, , 2000. A diverse range of splitting behavior has been associated with different subduction zones.…”
Section: Introductionmentioning
confidence: 99%